Y=10-2(6)

Simple and best practice solution for Y=10-2(6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=10-2(6) equation:


Simplifying
Y = 10 + -2(6)

Multiply -2 * 6
Y = 10 + -12

Combine like terms: 10 + -12 = -2
Y = -2

Solving
Y = -2

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Simplifying
Y = -2

See similar equations:

| X+2(3x+4)-5(6-7x)=8x+9 | | 5y=3x+12 | | 200x+27750=312.50x | | 3x+4(10-2x)=10 | | 10x+3(x-6)=x+30 | | 5x(2x-1)=35 | | 24=3(n-3) | | 11y-4=40 | | -3-3n=-n+3 | | ln(x+-3)+ln(x+2)=ln(x+-7) | | 1/5x+5h-1/5x | | -4m-13=5-m | | 6k+2=16+4k | | x+2=-68 | | 26=2x-14 | | (9i+11i)/10i | | Y-x=4x^2-8 | | -3-8x+7x=-3+5x | | 14=8z+6 | | log(7)16807=y | | 12m-71=25 | | 8p+4p+6=3p+7p | | 2x-x-3=5 | | 5b(b+4c)= | | x^2+0x+14=0 | | 247=-v+5(6v+3) | | 4y-9=27 | | 6(-1-6x)=246 | | 21/3=m/42 | | -343=-8(7-7a) | | 5(x-1)=5(4x-3) | | s^13t^8/s^2t |

Equations solver categories